Harnessing the power of natural minerals: A comprehensive review of their application as heterogeneous catalysts in advanced oxidation processes for organic pollutant degradation - Liu, Hongwen; Li, Xingyang; Zhang, Xiuxiu; Coulon, Frederic; Wang, Chongqing (Elsevier, 2023)
The release of untreated wastewater into water bodies has become a significant environmental concern, resulting in the accumulation of refractory organic pollutants that pose risks to human health and ecosystems. Wastewater treatment methods, including biological, physical, and chemical techniques, have limitations in achieving complete removal of the refractory pollutants. Chemical methods, particularly advanced oxidation processes (AOPs), have gained special attention for their strong oxidation capacity and minimal secondary pollution. Among the various catalysts used in AOPs, natural minerals offer distinct advantages, such as low cost, abundant resources, and environmental friendliness. Currently, the utilization of natural minerals as catalysts in AOPs lacks thorough investigation and review. This work addresses the need for a comprehensive review of natural minerals as catalysts in AOPs. The structural characteristics and catalytic performance of different natural minerals are discussed, emphasizing their specific roles in AOPs. Furthermore, the review analyzes the influence of process factors, including catalyst dosage, oxidant addition, pH value, and temperature, on the catalytic performance of natural minerals. Strategies for enhancing the catalytic efficiency of AOPs mediated by natural minerals are explored, mainly including physical fields, reductant addition, and cocatalyst utilization. The review also examines the practical application prospects and main challenges associated with the use of natural minerals as heterogeneous catalysts in AOPs. This work contributes to the development of sustainable and efficient approaches for organic pollutant degradation in wastewater.
Keywords: Natural minerals; Wastewater treatment; Advanced oxidation processes; Organic pollutants